Investigating Different Factors of Fear in Normal Delivery among Pregnant Women, in Arak -A Cross Sectional Study - Mahboubeh Khorsandi; Katayon Vakilian; Mona Nasir zadeh Masooleh (Fasa University of Medical Sciences, 2014)
Background ; Objective: This study was designed to investigate the causes and factors related to natural childbirth among pregnant women who attended prenatal care of Arak. Materials & Methods: This cross-sectional study   was carried out among 595 women who attended to prenatal care of Arak. Five hospitals were selected randomly. Only the pregnant women who wish to complete the questionnaire were enrolled in the study. The data were analyzed using chi-square test, t-test, the Mann-Whitney -u test, x2, Friedman Test through SPSS16 software. Results: The average sample age was 26 ±5.3 years. The mean score for nulliparous women on the Fear of Childbirth Questionnaire (26.2 ± 7.8) was significantly higher than that of multiparous women (23.9 ± 7.9), p<0.0 01. There was a significant difference between the scores of childbirth, women who chose the caesarian 27.5 ±5.1   and the women who chose natural childbirth 24.1±3.2 p= (0.02). The results indicated that the most common cause of fear was of the possible harm to the baby 77.9% (459). Conclusion: As far as the women's fear regarding child birth were mostly higher among nulliparous and cesarean women, it is recommended to make them aware about the causes of fear and provide consulting services in order to reduce the demand of caesarean as a way of childbirth.